Impresi Lupa dalam Taklif dan Implementasinya dalam Fikih Puasa Perspektif Mazhab Hambali : The Impression of Forgetting in Taklif and Its Implementation in the Jurisprudence of Fasting Perspective of the Hambali Mazhab - Akhmad Hanafi Dain Yunta; Sofyan Nur; Muhammad Nurtaufiq Sudirman (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This research aims to understand the concept of taklif and the nature of forgetting taklif in Islam, as well as to find out the consequences of sharia law for mukallaf forgets while fasting according to the perspective of the Hambali Mazhab. This research uses a library research type of research, which focuses on the study of manuscripts and texts, using research approaches in the form of a normative approach, a philosophical approach and a fiqh approach. The results of this research show several things, namely: First, taklif in Islam is an obligation required by religious law which includes obligatory, mandub, haram, makruh, and permissible. Taklif has three pillars, namely mukalif (the one who determines the law in this case is Allah Swt.), mukallaf (the person who is charged with Sharia law), mukallaf bih (actions that are charged to a mukalaf). Second, forgetting is one of the excuses that is justified in Islamic law, according to the Hambali Mazhab that someone who forgets is not said to be a mukallaf when he is in a state of forgetfulness. Third, forgetting about fiqh issues, especially fasting, has different legal consequences according to the Hambali Mazhab. Forgetting related to fasting has different legal consequences, including making the fast invalid and some not making a mukalaf's fast invalid. The implications of this research include being able to provide an explanation regarding the nature of taklif and forgetting in Islamic law that occurs in a mukallaf, regarding the taklif imposed by the sharia on him and being linked to the problems of forgetting in fasting jurisprudence and its consequences in sharia law according to the perspective of the Hambali Mazhab so that it becomes increasing knowledge insight for readers, especially science students and society in general.